A new modal lateral load pattern for improving pushover analysis to estimate nonlinear responses of structures. Issue 4 (2nd October 2022) - Habibi, Alireza; Izadpanah, Mehdi; Namdar, Yaser
ABSTRACT: Pushover analysis is a nonlinear procedure that is widely used as the primary tool for the nonlinear analysis of structures. In the conventional pushover method, the fundamental mode of the structure is selected as the dominant response mode of the multi degree of freedom (MDOF) system while neglecting the influence of higher modes. It has been proved that for many structures, higher vibration mode effects should be considered to boost the outcomes of the pushover analysis. In this study, a new Modal Load Pattern (MLP) is developed to improve pushover analysis procedure in estimating nonlinear responses of structures. For this purpose, MLP is defined by the directed algebraic combination of the weighted vibration mode-shape vectors of the structure. The weights of modes are determined using an optimisation algorithm such that the difference between the nonlinear responses of the structure under MLP and1 those of nonlinear time-history analysis is reduced to the minimum possible value. Comparing the outcomes of MLP with some well-known lateral load distributions shows that the proposed method increases the accuracy of responses resulting from pushover analysis. It is illustrated that against elastic behaviour, in the inelastic range of structural behaviour, it is likely that higher modes have a significant effect on the optimal lateral load distribution.